Data dissemination scheduling algorithm for V2R/V2V in multi-channel VANET - Xin PENG; Qingyong DENG; Shujuan TIAN; Haolin LIU; Wenwu XIE; Renfa LI (Tongxin xuebao)
Considering that the data dissemination in multi-channel VANET (vehicular ad hoc network),a cooperative data dissemination scheduling algorithm was introduced for V2R(vehicle to roadside unit) and V2V(vehicle to vehicle).The algorithm created initial scheduling operators according to data requisition of vehicles.Then,initial collision graph and collision matrix were generated based on the conflict among initial scheduling operators.After proving the positive semidefinite of collision matrix,SDP (semidefinite programming) was used to channel allocation and collision graph creation.The algorithm then assigned weights for each data requisition according to dwell time and data volume of vehicles in RSU service region.Furthermore,it selected maximum weighted independent set of collision graph.The goal was to satisfy the most urgent data requisitions by V2R/V2V cooperate transmission.Transportation simulation results demonstrate that the proposed solution effectively promotes the service capacity by utilizes the multichannel of VANET and V2R/V2V transmission scheduling.